Analisis Kecacatan Flakes pada Produk Oriflakes di PT Serealia Prima Nutrisia Daerah Istimewa Yogyakarta - Ningtyas, Farah Mustika; Kumalasari, Ika Dyah (Agriculture Faculty, 2024)
Product defects are one of the critical parameters to maintaining quality and consumer interest in marketed products. This study aims to determine the proportion of defects, types, and factors causing defects in flakes in Oriflakes products at PT Serelia Prima Nutrition suggestions for improvement are made to reduce the number of defective flakes. The method used to analyze defects that occur uses seven tools: control charts, Pareto diagrams, and fishbone diagrams. The number of flake defects is 14,8 kg for one month, the defects found in flakes are still under control because they do not cross the UCL and LCL limits. The types of flakes defects that occur are the color of the flakes that are too dark (burnt), too thick, lumpy, and the middle part is immature with the most dominant type of defect being the color of the flakes that are too dark (burnt) by 44%. Some of the leading causes of defective flakes are process and machine factors. Suggestions for improvements that can be made to prevent or reduce flakes defects are by always monitoring and checking the entire production process from weighing raw materials to the health of production tools and machines.